Faith, Finance, and Economy : Beliefs and Economic Well-Being - Akram, Tanweer; Rashid, Salim; Akram, Tanweer; Rashid, Salim (Singapore Springer Nature, 2020)
This open access book seeks to foster a multidisciplinary understanding of the ties between faith, financial intermediation, and economic progress by drawing on research across economics, finance, history, philosophy, ethics, theology, public policy, law, and other disciplines. Chapters in this edited volume examine themes as consequential as economic opportunities, real world outcomes and faith; values and consumerism; faith, financial intermediation and economic development in Western and Islamic societies; and the impact of faith issues on US workers, on the workplace and religion, and on the characteristics of good wealth. Though engaging with difficult questions, this book is written in an accessible style to be enjoyed by laypeople and scholars alike.
English
Keywords: Economics; Business ethics & social responsibility; Finance; Religious issues & debates; Macroeconomics; Financial services industry; Cultural Economics; Faith, Spirituality and Business; Personal Finance/Wealth Management/Pension Planning; Religion and Society; Macroeconomics/Monetary Economics//Financial Economics; Financial Services; Business Ethics; Personal Finance, Wealth Management, Pension Planning; Sociology of Religion; Macroeconomics and Monetary Economics; Theology and Economics; Christianity; Biblical stewardship; Islamic Finance; inequality; moral ecology; Open Access; Economics; Business ethics & social responsibility; Religious life & practice; Finance; Religious issues & debates; Macroeconomics; Monetary economics; Banking